Postcolonial studies in Slovakia and Hungary - KUŠNIR, Jaroslav (Porównania, 2015)
This overview article analyses the research in the field of postcolonial studies in Slovakia and Hungary and its institutional repre-sentation in both countries. The author of this article argues that in both countries the postcolo-nial theories have been mostly applied to the study of Irish,Canadian, Australian, and African literatures and cultures and mostly by scholars based at the universities’ English Departments; that the application of postcolonial theories in the study of both Slovak and Hungarian litera-tures and cultures have been rather marginal; and that a research in this field has rather been based outside English departments.